Who Rules America? Power, Politics, and Social Change - Domhoff G.William (MC Graw Hill, 2006)
Drawing from a power elite perspective and the latest empirical data, Domhoff’s classic text is an invaluable tool for teaching students about how power operates in U.S. society. Domhoff argues that the owners and top-level managers in large income-producing properties are far and away the dominant figures in the U.S. Their corporations, banks, and agribusinesses come together as a corporate community that dominates the federal government in Washington and their real estate, construction, and land development companies form growth coalitions that dominate most local governments. By providing empirical evidence for his argument, Domhoff encourages students to think critically about the power structure in American society and its implications for our democracy.